Geographical information system (GIS) modeling territory receptivity to strengthen entomological surveillance: Anopheles (Nyssorhynchus) case study in Rio de Janeiro State, Brazil - Albuquerque, Hermano Gomes (2018)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Doenças Parasitárias. Rio de Janeiro, RJ. Brasil / Fundação Oswaldo Cruz. Laboratório de Monitoramento Epidemiológico de Grandes Empreendimentos. Rio de Janeiro, RJ, Brasil.